Prophylactic effect of Kudingcha polyphenols on oxazolone induced colitis through its antioxidant capacities - Xingyao Long; Yanni Pan; Xin Zhao (Food Science and Human Wellness)
This research the preventive effect of Kudingcha polyphenols (Kp) on colitis based on animal experiments. Experimental mice divided into four groups, including normal group, model group, low-concentration Kp (LKP) group and high-concentration Kp (HKP) group, and they all smeared and given 0.15 mL 1% oxazolone solution by lavage to induce BALB/c mice colitis. DAI, colon weight/length ratio, serum levels of cytokines, related antioxidant activities of colon tissues such, and the mRNA expressions. The experimental results show that KP can significantly (p < 0.05) reduce DAI in mice with colitis and inhibit shortening of colon caused by colitis, increase colon weight/length ratio. It can also significantly reduce (p < 0.05) the activities of MPO, NO, MDA in mice colon tissues with colitis, increase the activity of GSH, and significantly increase (p < 0.05) the level of IL-2 and decrease the level of IL-10 in mice serum with colitis. The results of qPCR assay show that Kp can significantly increase (p < 0.05) the expression of Cu/Zn-SOD, Mn-SOD, GSH-Px, CAT, c-Kit, SCF and decrease the expression of IL-8, CXCR2 in mice colon tissues with colitis. Kp has a good preventive effect on colitis, and high concentration of PT has better preventive effect. Keywords: Kudingcha polyphenols, Oxazolone, Antioxidant, Colitis, mRNA expression